Study design and protocol for moving forward: a weight loss intervention trial for African-American breast cancer survivors. Issue 1 (December 2015) - Stolley, Melinda; Sharp, Lisa; Fantuzzi, Giamila; Arroyo, Claudia; Sheean, Patricia; Schiffer, Linda; Campbell, Richard; Gerber, Ben
Abstract Background Breast cancer survival rates are significantly lower among African-American women compared to white women. In addition, African-American women with breast cancer are more likely than white women to die from co-morbid conditions. Obesity is common among African-American women, and it contributes to breast cancer progression and the development and exacerbation of many weight-related conditions. Intervening upon obesity may decrease breast cancer and all-cause mortality among African-American breast cancer survivors. Methods/Design Moving Forward is a weight loss intervention being evaluated in a randomized trial with a projected sample of 240 African American breast cancer survivors. Outcomes include body mass index, body composition, waist:hip ratio, and behavioral, psychosocial and physiological measures. Survivors are randomized to either a 6-month guided weight loss intervention that involves twice weekly classes and text messaging or a self-guided weight loss intervention based on the same materials offered in the guided program. The guided intervention is being conducted in partnership with the Chicago Park District at park facilities in predominantly African-American neighborhoods in Chicago. Recruitment strategies include direct contact to women identified in hospital cancer registries, as well as community-based efforts. Data collection occurs at baseline, post-intervention (6 months) and at a 12-month follow-up. Discussion This study evaluates a community-based, guided lifestyle intervention designed to improve the health of African-American breast cancer survivors. Few studies have addressed behavioral interventions in this high-risk population. If successful, the intervention may help reduce the risk for breast cancer recurrence, secondary cancers, and co-morbid conditions, as well as improve quality of life. Trial registration U.S. Clinicaltrials.gov number:NCT02482506, April 2015